Coordination-induced metal-to-macrocycle charge transfer and effect of cations on reorientation of the CN ligand in the {SnL2Mac}2− dianions (L = CN−, OCN−, Im−; Mac = phthalo- or naphthalocyanine). Issue 15 (26th March 2019) - Konarev, Dmitri V.; Kuzmin, Alexey V.; Shestakov, Alexander F.; Khasanov, Salavat S.; Lyubovskaya, Rimma N.
Abstract : Anionic coordination {crypt(M + )}2 SnL2 Mac 2− complexes of tin(ii ) phthalo- (Pc) and naphthalocyanines (Nc) were obtained and discussed. Abstract : A series of anionic coordination complexes of tin(ii ) phthalocyanine (Pc) with cyanide, cyanate, and imidazolate (Im) anions (1, 3, and4, respectively) and tin(ii ) naphthalocyanine (Nc) with cyanide anions (2 ) has been obtained. Two anions coordinate to tin(ii ) atoms in1–4 to form the SnL2 Mac 2− dianions in salts with the general formula {crypt[2.2.2](M + )}2 SnL2 Mac 2− (M = K or Na; Mac: Pc or Nc; L = CN −, OCN −, Im − ). The coordination of two ligands to Sn II stabilizes these atoms in the higher tin(iv ) oxidation state, providing transfer of two electrons from Sn II to the macrocycle. The formation of tetraanionic (4−) macrocycles is accompanied by the appearance of new absorption bands in the NIR range, essentially blue-shifting both Soret and Q bands, and noticeable distortion in the macrocycles in2–4, showing alternation of the C–C and C–N bonds. However, such distortions are not observed in1 . The absence of alternation in the case of1 can be explained by the effect of uncompensated electric field from the surrounding cations, which stabilizes the macrocycle configuration with aligned bonds but nonuniform negative charge distribution on the imine nitrogen atoms. The cyanide ligand coordinates to SnPc by a nitrogen atom in1, forming a Sn–N bond of 2.339(1) Å in length, whereas the cyanide ligand coordinates to SnNc by a carbon atom in2, forming a shorter Sn–C bond of 2.266(3) Å in length. DFT calculations support the reorientation of the CN ligand in1, which is induced by the electrostatic field of closely located cations.